2019
DOI: 10.1038/s41467-019-09984-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation signatures of monozygotic twins clinically discordant for multiple sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory, demyelinating disease of the central nervous system with a modest concordance rate in monozygotic twins, which strongly argues for involvement of epigenetic factors. We observe highly similar peripheral blood mononuclear cell-based methylomes in 45 MS-discordant monozygotic twins. Nevertheless, we identify seven MS-associated differentially methylated positions (DMPs) of which we validate two, including a region in the TMEM232 promoter and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 75 publications
1
35
2
2
Order By: Relevance
“…Along this line, a Belgian survey using a large cohort of healthy individuals provided evidence of a profound impact of local environmental influences as reflected by cohabitation of nonrelated individuals (i.e., parents), which resulted in a 50% reduction in immunological variation between nonrelated individuals (18). Some of the nonheritable influences might lead to MS-associated epigenetic changes in immune cells, but these have yet to be characterized in detail (29). In our study, the observed strong effect of twinship is most likely driven by a combined effect of genetic and shared environmental influences because of the fact that all twin pairs in our study were raised together until adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, a Belgian survey using a large cohort of healthy individuals provided evidence of a profound impact of local environmental influences as reflected by cohabitation of nonrelated individuals (i.e., parents), which resulted in a 50% reduction in immunological variation between nonrelated individuals (18). Some of the nonheritable influences might lead to MS-associated epigenetic changes in immune cells, but these have yet to be characterized in detail (29). In our study, the observed strong effect of twinship is most likely driven by a combined effect of genetic and shared environmental influences because of the fact that all twin pairs in our study were raised together until adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Firre RNA primarily regulates autosomal genes in the hematopoietic system, including in common lymphoid progenitors (Andergassen et al, 2019;Lewandowski et al, 2019). This observation may prove relevant to sex differences in autoimmune disorders (Syrett and Anguera, 2019), as the FIRRE locus was also recently identified as differentially methylated in CD4 + memory T cells of twins discordant for multiple sclerosis (Souren et al, 2019). While global trans-acting FIRRE/Firre RNA functions are well beyond the scope of this perspective, it appears that many autosomal targets function in RNA splicing, processing and transport, likely due to FIRRE/Firre RNAs physical association with HNRNPU (Hacisuleyman et al, 2014;Bergmann et al, 2015).…”
Section: Dissecting Tandem Repeat Dna and Rna Functions In Vivomentioning
confidence: 98%
“…Human (clinical) genetics studies can help link FIRRE to novel roles outside of XCI. These results have revealed increased CTCF binding and chromatin accessibility across the FIRRE tandem repeat in females (Ding et al, 2014;Qu et al, 2015), as well as differential CpG methylation in multiple sclerosis (Souren et al, 2019). In closing, we want to raise the question whether conservation of CTCF-mediated superloops on the Xi may be merely a consequence of evolutionary selection for critical regulatory functions originating from the Xa?…”
Section: Firre Duplication As a Potential X-linked Intellectual Disabmentioning
confidence: 98%
“…Given the possibility of environment-and phenotypediscordant co-twin designs, epigenome-wide association studies with MZ twins offer greater power than studies with singletons, because MZ twins present essentially no variation in the DNA sequence itself. Such studies are recommended as a first step in the epigenetic analysis of human disease phenotypes (Rakyan et al, 2011), and notable recent examples include epigenomewide association studies of twins discordant for cerebral palsy (Mohandas et al, 2018), multiple sclerosis (Souren et al, 2019) and BMI (Li et al, 2019).…”
Section: Epigenetics and Twinsmentioning
confidence: 99%